IMPLEMENTATION OF ARTICLE 18 PARAGRAPH (3) OF REGIONAL REGULATION OF MALANG REGENCY NUMBER 7 YEAR 2010 ON POLLUTION AND ENVIRONMENTAL DAMAGE CONTROL RELATED TO UKL-UPL RECOMMENDATION - Jesika Dewi Rukmana (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Jesika Dewi RukmanaFaculty of Law, Universitas BrawijayaEmail: jesikadwi14@yahoo.co.idABSTRACTThe problem in this legal research is related to entrepreneurs who do not haveUKL-UPL document as business license which referred in Article 18 paragraph (3) ofRegional Regulation of Malang Regency Number 7 Year 2010 on Pollution and EnvironmentalDamage Control, but they still can run their business. This paper alsodiscusses about the actions taken by Government of Malang Regency through EnvironmentalAgency against illegal businesses which still operate. The type of thispaper is empirical legal research with sociological juridical approach, then it willbe analysed using descriptive analysis techniques based on primary and secondarydata.Â